2015
DOI: 10.3390/antib4040369
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of Tumor Necrosis Factor Alpha Receptors as a Therapeutic Strategy for Neurodegenerative Disorders

Abstract: Numerous studies have revealed the pleiotropic functions of tumor necrosis factor alpha (TNF-α), and have linked it with several neurodegenerative disorders. This review describes the signaling pathways induced by TNF-α via its two receptors (TNFR1 and TNFR2), and their functions in neurodegenerative processes as in Alzheimer's disease (AD), Parkinson's disease (PD), multiple sclerosis (MS), and ischemic stroke. It has become clear that TNF-α may exert divergent actions in neurodegenerative disorders, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 251 publications
(328 reference statements)
2
29
0
1
Order By: Relevance
“…This dual role of TNF signaling becomes particularly obvious in the central nervous system (5,6). Using the cuprizoneinduced mouse model of demyelination, it was shown that TNFR2 is critical for oligodendrocyte regeneration, whereas TNF signaling via TNFR1 promoted nerve demyelination (9).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This dual role of TNF signaling becomes particularly obvious in the central nervous system (5,6). Using the cuprizoneinduced mouse model of demyelination, it was shown that TNFR2 is critical for oligodendrocyte regeneration, whereas TNF signaling via TNFR1 promoted nerve demyelination (9).…”
Section: Resultsmentioning
confidence: 99%
“…Further, for neuronal cells, it was shown previously that proper TNFR2 activation induces protection from excitotoxicity in vitro (15,16); in the in vivo model analyzed here, in neurons in the vicinity of the acute insult and not immediately succumbing to excitotoxic death, competition of TNFRs for limiting amounts of endogenously produced membrane form of TNF exists, which results in suboptimal activation of TNFR2 of this cell population under a nontreatment condition. Moreover, at the level of intracellular signaling, it is known that signal cross-talk between TNFR1 and 2 exists in terms of competition for common signal transducers such as TRAF2 (33)(34)(35), with TNFR1 outperforming TNFR2 pathways in the case of abundance of soluble TNF, which triggers exclusively TNFR1 (3,6). In the presence of ATROSAB, neuronal response is shifted toward neuroprotective TNFR2 signaling because of blocked neuronal TNFR1, allowing the induction of a resistant state by endogenous tmTNF (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are different reports on the association between TNF protein family and human disorders such as cancers, immunogenic diseases, cardiovascular, nervous system, lung and metabolic disorders [4]. TNF-α induces cell apoptosis through binding to its receptor TNFR-1 [5].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been conducted on antitumor functions of the receptors [3]. The major difference between the two receptors has been reported to be the presence of a death domain in TNFR1 and absence of a death domain in TNFR2 [4]. TNF has been found to activate proapoptotic signaling cascade through TNFR1 [5] which is expressed in various types of cells, tissues [6] and tumors [7].…”
Section: Introductionmentioning
confidence: 99%